How to Compete in the Age of Artificial Intelligence : Implementing a Collaborative Human-Machine Strategy for Your Business /: Implementing a Collaborative Human-Machine Strategy for Your Business. (2018) - Mohanty, Soumendra; Vyas, Sachin
No abstract available